Environmental management and firm performance on firm value moderated by good corporate governance - Anggawikara, Sherly; Budidarma, I Gusti Agung Musa (Indonesian Journal of Multidisciplinary Science, 2023)
This research aims to analyze the influence of environmental management and firm performance on firm value, which is moderated by good corporate governance, which is proxied by board size and independent commissioners. The research design is quantitative research with the title "The Influence of Environmental Management and Firm Performance on Firm Value Moderated by Good Corporate Governance". The data source is secondary data collected from the IDX (Indonesian Stock Exchange) website to access financial report data of mining sector manufacturing companies, for the period 2017 - 2022. The population of this research is mining sector companies listed on the IDX for the 2017-2022 period. The sampling technique used in this research was purposive sampling. The results show that there is no direct influence from ISO certification on ROA (Return on Assets). There is a significant positive effect of firm value from the environmental management and firm performance variable, moderated by board size. However, the presence of independent commissioners does not moderate the effect of ISO and ROA on firm value. This means that the existence of directors can moderate the implementation of ISO 14001 on company value.